Vocational schools’ underrecognized role in PBL for sustainability : evidence from the German dual VET system - Hufnagl, Julia [Verfasser]; Annen, Silvia [Verfasser] (My University, 2026)
“Project-Based Learning (PBL) is a promising approach for sustainability education. This study adds to the current state of research by investigating PBL for sustainability in the German dual vocational system. The objective of this study was to determine (1) which role, in teaching sustainability, apprentices and pre-service teachers attribute to vocational schools and teachers and (2) what factors lead to the success of PBL for sustainability. The research design employs a triangulation approach that combines qualitative data from interviews and focus groups. The findings indicate that a shortage of resources, such as time and personnel, poses considerable challenges to PBL for sustainability in vocational schools. PBL for sustainability is considered an ancillary component that is desirable but does not align with the vocational school mandate of rapid learning success. Pre-service teachers acknowledge the significance of networks and learning location cooperation for PBL for sustainability, while apprentices prioritize the practical implementation of projects. The study results further demonstrate a strong connection between sustainability and personal relationships and interactions at school. Research and practice can take our findings as an opportunity to make greater use of the respective strengths of both learning locations in working together toward a sustainable future.” (authors’ abstract; BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; L 2.1 Lernformen; 370; Nachhaltige Entwicklung; Berufsschule; Unterrichtsgestaltung; Projektmethode; Projektunterricht; Lernortkooperation